Antibacterial activity of ethanolic extract and fraction of leaves of singawalang (Petiveria alliaceae) against resistant bacteria - Mulyani, Yani; Sukandar, Elin Yulinah; Adnyana, I Ketut (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
One of the plants that grow in Indonesia, and still does not use widely is singawalang (Petiveria alliaceae) from Phytolaceae family. Traditional herbal medicine preparations contained of Petiveria alliacea in the Caribbean, Latin America, West Africa and other regions for hundreds years has been used to treat pain, colds, inflammation, tumor, bacterial and fungal infection,hyperlipidemia, diabetes and other diseases. This study aims to determine the antibacterial activity of singawalang growth in Indonesia against resistant bacteria to antibiotics. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration(MBC) were determined by microdilution broth method and type of antibacterial action were determined by observing the profile of bacterial growth curve. Ethanol extract of dried leaves showed activity against bacteria i.e. MRSA (Methicillin-Resistant Staphylococcus aureus), MRCNS (Methicillin-Resistant Coagulase-Negative Staphylococci), VRE (VancomycinResistant Enterococcus). Further studies conducted by reviewing the type of work by looking at the growth curve and the observed changes in cell walls by scanning electron microscopy (SEM) at MRCNS (Methicillin-Resistant Staphylococcus coagulase-Negative). The results showed that ethanol extracts and all fractions showed good antibacterial activity against resistant bacteria, are bacteriostatic hexane fraction until the concentration of 8 MIC and change the morphology of the cell wall of MRCNS.Key words:Singawalang, Antibacteria, Broth Microdilution, bacterial growth curve, SEM